Amplified spontaneous emission and gain in highly concentrated Rhodamine-doped peptide derivative - Andrey Machnev (Nature Portfolio, 2021)
Abstract Bioinspired fluorescence, being widely explored for imaging purposes, faces challenges in delivering bright biocompatible sources. While quite a few techniques have been developed to reach this goal, encapsulation of high-quantum yield fluorescent dyes in natural biological forms suggest achieving superior light-emitting characteristics, approaching amplified spontaneous emission and even lasing. Here we compare gain capabilities of highly concentrated Rhodamine B solutions with a newly synthesized biocompatible peptide derivative hybrid polymer/peptide material, RhoB-PEG1300-F6, which contains the fluorescent covalently bound dye. While concentration quenching effects limit the maximal achievable gain of dissolved Rhodamine B, biocompatible conjugation allows elevating amplification coefficients towards moderately high values. In particular, Rhodamine B, anchored to the peptide derivative material, demonstrates gain of 22–23 cm−1 for a 10−2 M solution, while a pure dye solution possesses 25% smaller values at the same concentration. New biocompatible fluorescent agents pave ways to demonstrate lasing in living organisms and can be further introduced to therapeutic applications, if proper solvents are found.